Peripheralization of hemopoietic progenitors in primates treated with anti-VLA4 integrin. - Papayannopoulou, T (1993)
Interaction of hemopoietic cells with the elements of the underlying bone marrow stroma, the unique site of their "homing" in adult individuals, is essential for sustained normal hemopoiesis. However, the specific molecules responsible for homing and for the continuing interaction of hemopoietic cells with the bone marrow stromal cells in vivo, or those involved in progenitor/stem cell trafficking through the bloodstream, have not been defined. A large repertoire of adhesion receptors, especially of the integrin family, appear to play a prominent role in promoting adhesion of hemopoietic stem cells to cultured marrow stromal cells in vitro. To test the functional role of cytoadhesion molecules in vivo, we treated primates systemically with either anti-alpha 4- or anti-beta 2-integrin antibodies, whose antigens are found in the majority of hemopoietic progenitors and in many differentiated cells. We found that anti-alpha 4 (anti-VLA4, anti-CD49d) but not anti-beta 2 (anti-CD18) treatment selectively mobilized progenitors into the bloodstream (up to 200-fold). Peripheralization involved erythroid, myeloid, and mixed progenitors; was detectable 24 hr after a single anti-VLA4 injection; and lasted beyond the days of treatment. Anti-VLA4 treatment additively augmented peripheralization of progenitors in animals with a preceding course of granulocyte-colony-stimulating factor. These data provide insight on the involvement of VLA4 antigens in the in vivo trafficking of progenitors and are of relevance to collection of peripheral blood stem cells for transplantation.